THE EFFECT OF PARTICIPATORY BUDGETING, MANAGERIAL COMPETENCE AND UTILIZATION OF INFORMATION TECHNOLOGY ON THE IMPLEMENTATION OF RESPONSIBILITY ACCOUNTING, AND ITS IMPLICATIONS ON MANAGERIAL PERFORMANCE (A SURVEY OF PT BUMNIS IN WEST JAVA) - Syafdinal; Roeshartono Roespinoedji (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Efforts to achieve the intended target, the performance of managers for Strategic Industrial State Owned Enterprises (BUMNIS) need to do research on the performance of managers in the three BUMNIS as well as participatory budgeting, managerial competence and utilization of information technology and the implementation of responsibility accounting that affects it. This research is an explanatory research. Data collection by survey method is through questionnaire towards 61 respondents. Hypothesis testing using SEM analysis. The results of calculations performed using the LISREL program. The results of the study showed direct and indirect effects of participatory budgeting, managerial competence, and the use of information technology on the implementation of responsibility accounting by 76%. Direct and indirect effects of participatory budgeting, and managerial competencies, and the use of information technology on managerial performance by 94%. The effect of the implementation of responsibility accounting on managerial performance of 36%.